Ecological contribution of local Beauveria bassiana isolate to pest regulation and rice yield in tropical agroecosystems - MUHAMMAD RIADH ULUPUTTY; CHRISTOFFOL LEIWAKABESSY; NURENY GOO; ABRAHAM TALAHATURUSON; AMINUDIN UMASANGAJI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Uluputty MR, Leiwakabessy C, Goo N, Talahaturuson A, Umasangaji A. 2026. Ecological contribution of local Beauveria bassiana isolate to pest regulation and rice yield in tropical agroecosystems. Biodiversitas 27 (5): d270521. https://doi.org/10.13057/biodiv/d270521. The brown planthopper (Nilaparvata lugens) is a major pest in rice agroecosystems, causing significant yield losses. This study evaluated the effectiveness of a local Beauveria bassiana isolate in controlling planthopper populations and its potential implications for agroecosystem management under field conditions. The experiment was conducted in an organically managed rice field in Ambon, Indonesia, using a randomized block design with five treatments and five replications. Observations included apparent mortality, population density, attack intensity, and rice yield. The results showed that the application of B. bassiana increased apparent mortality from 15.2% in the control to 73.8-78.5% in treated plots, reduced population density from 139.1 to 30.4-42.6 individuals per plot, and decreased attack intensity from 60.3% to 5.3-6.1%. Rice productivity also increased from 4.52 t ha⁻¹ in the control to 5.84-6.12 t ha⁻¹ following fungal application. However, mortality was assessed as apparent mortality based on population reduction, and no direct confirmation of fungal infection or environmental variables was conducted. These findings suggest that locally adapted entomopathogenic fungi can contribute to pest regulation, support microbial biodiversity, enhance sustainable rice production, and strengthen ecologically based integrated pest management strategies in tropical agroecosystems under diverse environmental conditions.